2019
DOI: 10.1017/s095252381800007x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of visual function in Royal College of Surgeon rats using a depth perception visual cliff test

Abstract: Preserving of vision is the main goal in vision research. The presented research evaluates the preservation of visual function in Royal College of Surgeon (RCS) rats using a depth perception test. Rats were placed on a stage with one side containing an illusory steep drop (“cliff”) and another side with a minimal drop (“table”). Latency of stage dismounting and the percentage of rats that set their first foot on the “cliff” side were determined. Nondystrophic Long–Evans (LE) rats were tested as control. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We can hypothesize that this phenotype penetrance is linked to the retino-geniculo-cortical pathway state in absence of FMRP. Indeed, it has been clearly demonstrated that modification of this pathway by targeting the retina or the visual brain areas modulate depth perception (Mazziotti et al, 2017; Tzameret et al, 2019). From a molecular standpoint, the decreased efficiency of the retino-geniculo-cortical pathway in Fmr1 −/y mice must be linked to the impairments of neuron-specific functions such as glutamate/GABA pathways or synaptic transmissions (Davidovic et al, 2011; Doll et al, 2017) due to well described protein deregulation in FXS conditions, such as PSD95, mGlur5, or SNARE complex expression defects (Zhu et al, 2011; Westmark, 2013; Tang et al, 2015; Aloisi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that this phenotype penetrance is linked to the retino-geniculo-cortical pathway state in absence of FMRP. Indeed, it has been clearly demonstrated that modification of this pathway by targeting the retina or the visual brain areas modulate depth perception (Mazziotti et al, 2017; Tzameret et al, 2019). From a molecular standpoint, the decreased efficiency of the retino-geniculo-cortical pathway in Fmr1 −/y mice must be linked to the impairments of neuron-specific functions such as glutamate/GABA pathways or synaptic transmissions (Davidovic et al, 2011; Doll et al, 2017) due to well described protein deregulation in FXS conditions, such as PSD95, mGlur5, or SNARE complex expression defects (Zhu et al, 2011; Westmark, 2013; Tang et al, 2015; Aloisi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, children in group B accepted the conventional visual function rehabilitation training, a new pair of glasses was prescribed for each child by a professional optometrist for refraction correction, the routine quantitative cover was carried out, and by combining the family therapy with clinical treatment, an individualized diagnosis and treatment plan was made by the physician for the children to visit our clinic and finish corresponding tests and training. e specified fine training tasks including threading a needle, delineating practice, and stringing small beads were finished at home, the children revisited the clinic regularly, and their files were recorded [9,10].…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Additionally, for a comprehensive evaluation of the neurological clinical symptoms associated with damage to different brain regions due to repeated severe hypoglycemic episodes, more extensive clinical assessments are necessary. In this study, initial assessments of visual acuity in rats were carried out using the optokinetic response test [ 40 , 41 ] and the visual cliff test [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%